Perfluorooctanoic acid (PFOA) exposure in relation to the kidneys: A review of current available literature - Liu, Dongge; Yan, Shuqi; Wang, Pingwei; Chen, Qianqian; Liu, Yanping; Cui, Jiajing; Liang, Yujun; Ren, Shuping; Gao, Ying (Frontiers in Physiology, 2023)
Perfluorooctanoic acid is an artificial and non-degradable chemical. It is widely used due to its stable nature. It can enter the human body through food, drinking water, inhalation of household dust and contact with products containing perfluorooctanoic acid. It accumulates in the human body, causing potential harmful effects on human health. Based on the biodegradability and bioaccumulation of perfluorooctanoic acid in the human body, there are increasing concerns about the adverse effects of perfluorooctanoic acid exposure on kidneys. Research shows that kidney is the main accumulation organ of Perfluorooctanoic acid, and Perfluorooctanoic acid can cause nephrotoxicity and produce adverse effects on kidney function, but the exact mechanism is still unknown. In this review, we summarize the relationship between Perfluorooctanoic acid exposure and kidney health, evaluate risks more clearly, and provide a theoretical basis for subsequent research.